Gentes de ascendencia africana en el espacio relacional de los portugueses limeños, 1571-1695 - Sullón Barreto, Gleydi (2025)
This article looks at the social space of the Portuguese people who lived in Lima between 1571 and 1695, focussing on their connections with the people of African origin. From the analysis of notarial documents and several marriage records it has been known that the Portuguese, although they were not large owners of slaves, did keep a few pieces among their property. Thus, the domestic space is the first sphere of these relationships. Outside of it, we find other spaces such as the «pulperías» or certain workshops, which concentrated people of a very diverse origin and ethnicity. The debts for and against indicated by the Portuguese in their wills show that they also had economic dealings with people of African descent. This means that viceregal societies were not static, and that regardless of the categories into which the subjects could be classified, communication between them was fluid, dynamic and, at times, unforeseen.